The Treatment Alliance and the Provision of Removable Dentures: Exploring the Emotional Work of the Dental Team - Barry John Gibson; Sarah R. Baker; Tom Broomhead; Bilal El-Dhuwaib; Nicolas Martin; Heba R. Salama; Gerry McKenna; Anousheh Alavi (MDPI AG, 2024)
Background: Research has demonstrated that the loss of one or more natural teeth can be an emotionally traumatic experience that mirrors processes associated with bereavement. There remains scant literature examining the role of emotions in dental encounters. One such exception is the literature on the idea of the 'treatment alliance' in dental encounters. The aim of this paper is to explore the role of the 'treatment alliance' in dentist-patient encounters. Methods: Data were collected from clinical observations, semi-structured interviews and focus groups exploring the experience of tooth loss and how the treatment alliance shaped the patient journey. Data analysis was conducted using the grounded theory method influenced by phenomenology. Coding was conducted using NVIVO and the unit of analysis was the treatment alliance. Results: Twenty participants took part in the interviews (eleven male; nine female; 22-86 years; mean age = 58.9 years). Observations were carried out with a further fourteen participants (seven male; seven female; 50-101 years; mean age = 62.2 years). The paper draws on four cases taken from the observational data to illustrate important dynamics underpinning how the treatment alliance varied. These case studies are then used as the basis for a critical discussion of the importance of the treatment alliance in dentistry. Conclusions: The treatment alliance acted as an important moderator in the clinical encounter, helping to influence successful outcomes. An important foundational component of the treatment alliance was the degree of emotional work the dental team conducted when 'getting to know' unfamiliar patients. Whilst emotions were an important factor in dental encounters, their acknowledgement and management were not essential to all successful outcomes. Much more research is therefore needed into the role of emotional labour in dental encounters.